From Humours to Metabolism: An Integrative Review of Obesity Management in Unani Medicine - Faiqa Rather; Sadique Ali; Mubashra Khan; Imran Khan (International Journal of Nutritions, 2026)
Unani Medicine, a traditional complementary and alternative medicine (CAM) system, adopts a holistic, temperament-based approach to disease prevention and management. In classical Unani literature, obesity is described as Simān-e-Mufriṭ, a pathological condition arising from humoral imbalance, particularly the predominance of phlegm (Balgham) and derangement of temperament (Su’-e-Mizāj), most commonly of a cold and moist nature. This condition is attributed to a sedentary lifestyle, weakened digestive and metabolic faculties, and excessive consumption of calorie-dense, fatty foods. The present narrative review aims to elucidate the Unani concept of obesity, with emphasis on its etiopathogenesis and traditional management strategies, and to explore their relevance in contemporary obesity management. Classical Unani texts, including Al-Qānūn fī’l-Ṭibb, Kitāb al-Ḥāwī fi’l-Ṭibb, Kāmil al- Ṣanāʿa, Firdaws al-Ḥikma fi’l-Ṭibb, Kitāb al-Kulliyyāt, Ṭibb-i-Akbar, and Iksīr-i-Aʿẓam, were reviewed, along with contemporary scientific literature retrieved from PubMed, ScienceDirect, Wiley Online Library, and Google Scholar. Unani Medicine conceptualizes obesity as a disorder characterized by excess Balgham and impaired metabolic faculties. Management is primarily based on dietotherapy (Ilāj bi’l-Ghizā’), regimenal therapy (Ilāj bi’l-Tadbīr), and pharmacotherapy (Ilāj bi’l-Dawā’), individualized according to temperament and disease severity. The Unani system thus offers a comprehensive and personalized framework for obesity management, and its principles may serve as valuable complementary strategies alongside conventional approaches, warranting further pharmacological validation and well-designed clinical trials.
Keywords: Complementary Medicine; Humoral imbalance; Regimenal Therapy; Simān Mufriṭ; Unani medicine; obesity